A Novel Expansin Protein from the White-Rot Fungus Schizophyllum commune - Tovar Herrera, Omar Eduardo; Batista García, Ramón Alberto; Sánchez Carbente, María del Rayo; Iracheta Cárdenas, María Magdalena; Arévalo Niño, Katiushka; Folch Mallol, Jorge Luis (Public Library of Science, 2015)
A novel expansin protein (ScExlx1) was found, cloned and expressed from the Basidiomycete fungus Schizophylum commune. This protein showed the canonical features of plant expansins. ScExlx1 showed the ability to form “bubbles” in cotton fibers, reduce the size of avicel particles and enhance reducing sugar liberation from cotton fibers pretreated with the protein and then treated with cellulases. ScExlx1 was able to bind cellulose, birchwood xylan and chitin and this property was not affected by different sodium chloride concentrations. A novel property of ScExlx1 is its capacity to enhance reducing sugars (N-acetyl glucosamine) liberation from pretreated chitin and further added with chitinase, which has not been reported for any expansin or expansin-like protein. To the best of our knowledge, this is the first report of a bona fide fungal expansin found in a basidiomycete and we could express the bioactive protein in Pichia pastoris.